PENGARUH MODEL PBL DENGAN PENDEKATAN STEM TERHADAP KOMPETENSI KOGNITIF PESERTA DIDIK PADA MATERI SISTEM PENCERNAAN KELAS XI DI SMA/MA - Heru Ardiansyah; Jhon Riswanda; Fahmy Armanda (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
The learning model with an approach that can be used to achieve cognitive success is by using the PBL model with the STEM approach. This study aims to determine the effect of the PBL model with the STEM approach on the cognitive competence of students in the digestive system material for class XI in SMA / MA. This research was conducted from January to February 2021. The method in this study was a real-time experiment or pre-experimental one group pre-test - post-test design. Pre - experimental one group pre-test - post-test design. The population in this study were students of class XI. The sample in the study consisted of 18 students who were an experimental class taken using test techniques. The test technique here is an objective test, namely multiple choice and essays or questions about this technique will be carried out before and after the research (pretest and posttest). The data in this study were obtained from a number of quantitative data, namely the cognitive aspects obtained from the pre-test and post-test scores. After the data has been obtained, the next step is to analyze the data. This can be seen from the results of the t-test used to calculate the hypothesis and test the level of effectiveness. The results showed that the PBL model with the STEM approach showed differences in the cognitive competences of students. This can be proven by the 2 tailed significance value is 0.000, which is less than 0.05, which means that H0 is rejected and Ha is accepted. Data analysis techniques can be proven by the results of the N-gain test value. This can be proven by the difference between the pre-test and post-test results of the experimental class, namely 46.5 - 65.3 = 33.67%. Conclusion. That the PBL learning model with the STEM approach has an effect on the results of students' cognitive competencies is acceptable. This can be proven by the normality, homogeneity, t-test and N-gain test. The effect of the application of PBL model learning with the STEM approach is a moderate criterion.